Pengaruh Strategi Pengelolaan Dan Pemasaran Industri Lokal Sarung Hitam (Le’leng) Terhadap Pendapatan Masyarakat Kajang Amma Towa Di Kabupaten Bulukumba - Moh. Arga Wijana; Muh. Irwan Suaeb (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
If you look at the conditions of the IKM business climate in Bulukumba, it has not experienced such a significant development (stagnant). Based on the review of the main problem, the research objectives to be achieved are as follows: To determine and analyze the influence of local industrial management strategies on the income of the Kajang Amma Towa community. To find out and analyze the influence of marketing on the income of the people of Kajang Amma Towa. To find out and analyze the influence of local industry management strategies and marketing on the income of the Kajang Amma Towa community. The research location is in the Amma Towa Kajang Customary Area, Tanah Towa Village, Kajang District, Bulukumba Regency. This study uses descriptive qualitative research methods, with data sources, namely questionnaires and documentation. The sample of this research is village apparatus. The data analysis used is data quality test, classical/prerequisite test, and hypothesis testing. Local industry management strategies have a positive and significant impact on people's income. With a sig value of 0.001 < 0.05, which means that there is a significant relationship between local industrial management strategies and the income of the Kajang Amma Towa community in Bulukumba Regency. The marketing strategy has a significant effect on the income of the Kajang Amma Towa community. The results of the study concluded that the hypothesis which reads